CRAFT BEER AND HUMAN HEALTH: EVALUATION OF THEANTIOXIDANT PROPERTIES AND THEIR BENEFITS - Ribeiro, Dário Martins; Heimbecher, Catia Terezinha (Seven Editora, 2025)
Craft beer is linked to the search for more natural, differentiated and high-quality products. In this study, he investigated, through a literature review, the antioxidant properties of craft beer and the benefits associated with its moderate consumption, especially in cardiovascular health. The antioxidants present in craft beers, such as polyphenols, flavonoids, and malt, contribute to the neutralization of free radicals and the reduction of oxidative stress. The results of the review point out that moderate consumption of craft beers can help prevent cardiovascular diseases, such as atherosclerosis, hypertension and heart attacks, due to the bioactive properties provided by their ingredients and differentiated production processes. systematic approach to identify and select articles related to the antioxidant properties of craft beer and its potential health benefits. The searches were carried out in the Virtual Health Library (VHL), exploring databases such as MEDLINE, VERTIDEX, LILACS and WPRIM, the keywords used were Beer, Antioxidants, Malt and Polyphenols. Inclusion criteria were established for articles published between 2018 and 2024, After the screening process, which involved analysis of titles, abstracts, and full reading, 10 articles were selected to compose the final portfolio. The analysis highlighted topics such as the chemical composition of craft beer, the impact of ingredients such as malt and hops, and the relationship of these compounds to cardiovascular health. The choice of articles sought a representativeness that covered biochemical, therapeutic and production aspects. DOI: https://doi.org/10.56238/sevened2025.018-043